The Formation of the Future Specialist Professional Culture in the Educational Space of the University. - Нікула, Наталія; Бражанюк, Андрей (In O. Clipa (vol. ed.), Lumen Proceedings: Vol. 16. ATEE 2020 - Winter Conference. Teacher Education for Promoting Well-Being in School. Suceava, 2020 (pp. 332-349). Iasi, Romania: LUMEN Publishing House., 2020)
The article highlights the theoretical foundations on the formation of future specialist professional culture the in the field of professions "person-person". It is established that this is a purposeful, specially organized influence on the individual to improve his/her motivational sphere, value orientations, professional knowledge, skills and abilities, ability to empathy and reflection. This problem was studied by the author from the view of several scientific approaches: axiological, cultural, competence, activity. Based on the definitive analysis, the "professional culture of a specialist" concept is formulated, which is considered as a combination of professional and personal values and qualities of a specialist, his/her professional competence, which ensure highly effective fulfilment of professional duties based on reflection and self-development. Structural and semantic analysis allowed identifying components of the professional culture of future professionals i.e. value, cognitive, personal, and reflexive. The experimental research diagnostic tools of a formation condition of the future specialist professional culture in educational space of university are developed and tested: criteria, indicators, levels, techniques which reflect integrity of the investigated phenomenon structural components.
Keywords: conditions; professional culture; competence